The Influence of Climatic Factors on Semen Parameters of Merino Rams in A Tropical Environment - Ismaya (Ismaya); Phillip Summers (Faculty of Animal Science, Universitas Gadjah Mada, 2005)
File lengkap ada dalam bentuk PDF dibawah ini